Family and Childcare Support Public Expenditures and Short-Term Fertility Dynamics - Enache, Cosmin (Panoeconomicus, 2013)
In a period of very low fertility, effective family and childcare support policy measures are needed. From a wide range of instruments available to government intervention, we focus on public expenditures effects on short-term fertility. Using a sample of 28 European countries in a panel framework, we found that there is a small positive elasticity of crude birth rate to cash benefits related to childbirth and childrearing provided through social security system. Different public services provided to ease the burden of parents and all other benefits in kind, means or non-means tested, are found to be insignificant. These results are robust to alternative methods of estimation. Controlling for country heterogeneity by religion and by culture, some particularly interesting differences in birth rate determinants were highlighted as well.Key words: Social security, Fertility.JEL: H55, I38.